The Conceptual Metaphor Analysis in the Song Lyrics “Is You” by Jay Chang (2020) - Fadhila, Naura; Juanda, Juanda (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
The objective of this study research is to investigate the manner in which metaphors are communicated in song lyrics through the application of conceptual metaphor theory, which consists of source and target data and aims to clarify how abstract concepts are conceptualized and comprehended. By employing a descriptive qualitative research method and conceptual theory, this study achieves coherent and systematic findings. The data used is a song from Jay Chang entitled "Is You". The data produced in this research comprises metaphors that have the potential to aid in the creation of vivid, realistic, and memorable imagery in the composition of songs that symbolize elaborate emotional experiences or concepts. The results show that the categorization of target domains found in the song is three, namely, Romantic Relationships, Mental Imagery or Memory, and Difficult Relationships. Keywords: Conceptual Metaphor, Descriptive Qualitative, Conceptual Theory